Declining US life expectancy since covid-19—structural inequities foreshadow future fallout. (16th September 2022) - Noppert, Grace A; Duchowny, Kate A; Clarke, Philippa J
Abstract : The latest data on US life expectancy form part of a larger pattern of languishing population health, say Grace Noppert and colleagues